Exploring the associations between the biomechanical and psychological mechanistic pathways of lower back pain development amongst persons with lower-limb amputation: A study protocol. - Alexandra Withey; Dario Cazzola; Abby Tabor; Elena Seminati (PLoS ONE)
Introduction The global rise in lower-limb amputations is mainly due to diabetes and vascular complications. Amputations cause serious physical and psycho-social disabilities which impair locomotion and compromise patients quality of life. Biopsychosocial factors such as altered gait parameters, poor prosthetic fit, depression, fear avoidance behaviours and stigma increase the risk of individuals incurring lower back pain; the leading cause of secondary disability amongst persons with lower-limb amputation. Exploring the potential mechanistic pathways of lower back pain development is important to inform timely patient-centred programmes of care. Currently, limited information exists to inform the design of such programmes. Thus, there is a pressing need to understand the bio-behavioural, psychological, and social features of individuals with lower-limb amputation in the presence of lower back pain. Methods and analysis This proposed study protocol employs a prospective longitudinal study design that aims to explore the determinants of lower back pain amongst 30 adults with unilateral lower-limb amputation over 12-months. Biomechanical gait variables, trunk and lower-limb muscle activations, and objective pain measurements will be monitored every 3-months, and their relationship will be investigated. This information can be used to explore the characteristics of lower back pain and will inform future care management and rehabilitation processes. A data repository will be created and will be accessible through the University of Bath library website (https://library.bath.ac.uk/home). Trial reference number The study is registered at IRAS ID: 321729 and at ClinicalTrials.gov: NCT06243549.